Building an Anti-Corruption Legal Culture - Syah, Kaharuddin; Malik, Abdul (International Journal of Criminology and Sociology, 2021)
Background: Corrupt behaviour in Indonesia is increasingly becoming a culture, which is undoubtedly destructive to the economy and moral order of the nation. Corruption has become a chronic disease in the country, which requires serious treatment, especially by the state. Objective: Building an anti-corruption culture is a genuine and sustained intention; such an effort should be spearheaded y the government. Instilling an understanding that corruption is a despicable act based on religious and social norms which are not ethical. However, corruption’s complexity and its modes or categories have kept on the increase along with the vast power of the state in regulating social life. Various attempts have been made by all the previous governments, but they cannot free the country from the tsunami of corruption. Approach: Though the various policies and law enforcement models have been put in place, corruption persists today. The strategy of building an anti-corruption legal culture should be continuously promoted, in securing a corruption-free future for Indonesia.